P-P24 Optimising post-operative nutrition in patients undergoing pancreaticoduodenectomy. (16th December 2021) - Gray, Katie; Rana, Mridul; Ceresa, Carlo; Udupa, Venkatesha; Soonawalla, Zahir; Silva, Michael; Friend, Peter; Reddy, Srikanth
Abstract: Background: A considerable number of patients undergoing pancreaticoduodenectomy require supplemental nutrition in the postoperative period. However, there remains no national consensus on the optimal postoperative supplemental feeding modality. Furthermore, at our institution a variation in practice exists when considering post-operative entera (via the naso-jejunal (NJ)) or parenteral nutrition (PN). This study aimed to evaluate the utility of post-operative enteral or parenteral nutrition at our centre and to explore risk factors predisposing patients to post-operative nutritional deficits requiring supplementation. Methods: We retrospectively analysed the electronic case records of all patients undergoing a pancreaticoduodenectomy between November 2019 and November 2020 at our HPB specialist centre. Key patient demographic data and post-operative nutritional requirements with route, length and indication for supplemental feeding as well as biochemical markers, length of stay (LoS) and complications were collected and analysed. Data were analysed via intention to treat analysis. Results: 48 patients underwent a pancreaticoduodenectomy, of which 26 had an NJ tube inserted intra-operatively. 16 (33%) patients required supplemental feeding, via NJ route in 7 and PN in 9. 2 patients were intolerant to NJ feeds and progressed to PN. NJ fed patients had shorter LoS (12(10-42) vs. 28(14-63) days)(p = 0.09) compared to PN feeding. PN-related line infection or thrombosis in 4 (36%) patients. Supplemental feeding met daily kcal requirements in 13 (81%) patients, but PN was associated with greater weight loss (-5%) than NJ feeding (-3%). Significantly increasing the risk of needing supplemental nutrition: advanced age(p = 0.04), ASA≥2(p = 0.04) and anastomotic leak(p = 0.02). Conclusions: In this group of patients, NJ feeding was largely well-tolerated and the majority of patients met their required daily kcal via this route. Due to the increased incidence of complications associated with PN, NJ feeding should be considered as the 1 st line option for post-operative nutritional supplementation, with intra-operative insertion of an NJ tube considered for higher-risk patients.